Sea urchin-like CoNi2S4 materials derived from nickel hexamyanocobaltate for high-performance asymmetric hybrid supercapacitor. (26th November 2022) - Wu, Shang; Xu, Xin; Yan, Xiangtao; Zhao, Huanlei; Liu, Chaoyang; Wang, Yanbin; Su, Qiong; Yin, Fenping; Yang, Quanlu
Abstract: In this work, a mild chemical precipitation method and simple hydrothermal treatment of the nickel hexamyanocobaltate precursor strategy are developed to prepare a sea urchin-like CoNi2 S4 compound with remarkable specific capacity and excellent cycling stability. The prepared CoNi2 S4 has an outstanding specific capacity of 149.1 mA h g −1 at 1 A g −1 and an initial capacity of 83.1% after 3000 cycles at 10 A g −1 . Moreover, the porous carbon nanospheres (PCNs) with exhibit cycling stability (94.7% of initial specific capacity after 10 000 cycles at 10 A g −1 ) are selected as negative electrode to match CoNi2 S4 positive electrode for assembly of CoNi2 S4 //PCNs asymmetric supercapacitor (ASC). Satisfactorily, the as-assembled CoNi2 S4 //PCNs ASC exhibits an impressive energy density of 41.6 Wh kg −1 at 797 W kg −1, as well as the suitable capacity retention of 82.8% after 10 000 cycles. The superior properties of the device demonstrated that the as-prepared material is potential energy storage material.